The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1002/ange.200902672
|View full text |Cite
|
Sign up to set email alerts
|

Anwendung von Poly(ethylenglycol) beim Wirkstoff‐Transport: Vorteile, Nachteile und Alternativen

Abstract: Im stetig wachsenden Feld der Polymer‐basierten Wirkstoff‐Transport‐Systeme gilt Poly(ethylenglycol) (PEG) als der Goldstandard für Stealth‐Polymere. Welche Eigenschaften PEG aufweist, die diese herausragende Stellung rechtfertigen, soll in diesem Aufsatz diskutiert werden. Die ersten PEGylierten Produkte erschienen bereits vor 20 Jahren auf dem Markt. Seither konnten viele Erkenntnisse in klinischen Untersuchungen gewonnen werden, allerdings wurden dabei nicht nur Vorteile festgestellt, sondern auch mögliche … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
46
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(52 citation statements)
references
References 211 publications
(288 reference statements)
0
46
0
4
Order By: Relevance
“…[21][22][23][24][25][26] To date, PEG, also referred to as poly(ethylene oxide) (PEO) for molecular weights above 20 000 g mol À1 , is the established reference polymer for pharmaceutical and biomedical applications, because of 1) its excellent solubility in both aqueous and organic media, 2) the fact that it displays no immunogenicity, antigenicity, or toxicity and 2) the high flexibility and hydration of the main chain. [27][28][29][30] Often PEG is…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24][25][26] To date, PEG, also referred to as poly(ethylene oxide) (PEO) for molecular weights above 20 000 g mol À1 , is the established reference polymer for pharmaceutical and biomedical applications, because of 1) its excellent solubility in both aqueous and organic media, 2) the fact that it displays no immunogenicity, antigenicity, or toxicity and 2) the high flexibility and hydration of the main chain. [27][28][29][30] Often PEG is…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were obtained by Salvati et al, where transferrin-targeted silica nanoparticles also experienced a reduction in binding specificity after exposure to serum. [11] Once we had confirmed that serum protein effectively reduced the targeting specificity of Herceptin-conjugated nanoparticles towards ErbB2+ cells, we determined whether Figure 1. Binding specificity is reduced by serum-protein adsorption but this effect is alleviated by PEG backfilling.…”
mentioning
confidence: 98%
“…[10] To suppress protein adsorption, researchers often functionalize the nanoparticle surface with the antifouling polymer polyethylene glycol (PEG). [11] In order to properly design target-specific nanoparticles, a detailed understanding of the amount of PEG to apply and type of PEG to use is essential to effectively reduce serum-protein-nanoparticle interactions.…”
mentioning
confidence: 99%
“…[6] Unfortunately,m ost available stimuli-responsive systems have alimited chance of reaching clinical trial owing to the complexity of architectural design, difficulties in the scaling up,and potential toxicity concerns. [7] At ypical polymeric and nano-therapeutic based on these polymers is Genexol-PM, which is approved in South Korea and is undergoing clinical investigation in the United States. [7] At ypical polymeric and nano-therapeutic based on these polymers is Genexol-PM, which is approved in South Korea and is undergoing clinical investigation in the United States.…”
mentioning
confidence: 99%